2015
DOI: 10.1002/hed.23857
|View full text |Cite
|
Sign up to set email alerts
|

Management of the compromised airway and role of tracheotomy in anaplastic thyroid carcinoma

Abstract: Tracheotomy can facilitate completion of palliative treatment in those patients with ATC and stridor. Given the short life expectancy of these patients, a balanced decision must be made regarding the role and timing of tracheotomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 13 publications
0
13
0
1
Order By: Relevance
“…Once a fistula develops, frequent dose interruptions are required to prevent the spread of the fistula (29). Recent guidelines published by the ATA discuss the management of the compromised airway in such patients, and suggest that a tracheotomy should be performed to secure the airway in circumstances of life-threatening airway obstruction (30). Airway compromise with a thyroid mass may be a presenting feature of ATC, or it may occur in a patient with a pre-existing diagnosis of the disease (30).…”
Section: Discussionmentioning
confidence: 99%
“…Once a fistula develops, frequent dose interruptions are required to prevent the spread of the fistula (29). Recent guidelines published by the ATA discuss the management of the compromised airway in such patients, and suggest that a tracheotomy should be performed to secure the airway in circumstances of life-threatening airway obstruction (30). Airway compromise with a thyroid mass may be a presenting feature of ATC, or it may occur in a patient with a pre-existing diagnosis of the disease (30).…”
Section: Discussionmentioning
confidence: 99%
“…Another problem is the displacement of the trachea due to the compression effect of the mass during tracheotomy. ATA recommends that tracheotomy should be performed under operating conditions and under general anesthesia as we did in our case (3)(4)(5)(6)(7)(8)(9)(10)(11).…”
Section: Discussionmentioning
confidence: 79%
“…In sagittal view of computed tomography scan of head and neck; it is observed that the same mass has filled the thyroid space and narrowed the tracheal lumen Figure 3. A view of tracheotomy after partially tumor excision of the istmus region, severe destructive mass in the trachea drastically eliminated the anatomical guiding points found to be shorter than in patients who underwent "debulking" surgery (9). However, it is important to note that in patients with ATC, respiratory problems are likely to occur until the tracheotomy stage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Критически важно после постановки диагноза подробно объяснить пациенту и его семье, как будет развиваться его заболевание, предупредить их о риске развития удушья, описать пути его предотвращения и устранения. Трахеостомия лишь временно решает эту проблему, и часто пациент считает ее болезненной и эмоционально непереносимой, поэтому может не дать согласия на ее выполнение [19,23]. Пациенты, испытывающие сложности с глотанием пищи, могут нуждаться в энтеральном питании.…”
Section: Introductionunclassified